OFF LIMITS OFF-THE-JOB PRIVACY STILL EXISTS FOR MOST WORKERS, BUT TWO IN FIVE GIVE EMPLOYERS LESS THAN TOP MARKS (Tufts Archival Research Center, 2007)
Press release presenting results of survey on off-the-job privacy and announcing a documentary released in conjunction entitled "OFF LIMITS: Your Health, Your Job, Your Privacy". Discusses employees’ concerns that employers are abusing health and lifestyle information to cut health care costs in terms of claims to insurance companies. Specifies heightened concerns of African Americans and low-income workers in off-the-job invasion of privacy.